PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MELALUI MODEL PENEMUAN TERBIMBING DI KELAS VII.2 SMP NEGERI 4 LAHAT - RAHMAWATI RAHMAWATI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2023)
The application of the guided discovery model is expected to improve learning outcomes and increase student attention and activity in the learning process. This study aims to determine the increase in student learning outcomes after the implementation of the guided discovery model, as well as improve the learning process carried out in class, and improve teacher performance. This research uses classroom action research (classroom action research) as many as three cycles. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is class VII.2 students. The data obtained were in the form of final test results, observation sheets of teaching and learning activities. The results of the research show that the application of the guided discovery model has improved student learning outcomes. This increase can be seen in details of 55.56% in cycle I with a class average of 71.15, with the highest score of 80 and the lowest score of 50. In cycle II 74.07% with a class average of 74.67 with the highest score of 85 and the lowest score is 60 and in cycle III 92.59% with a class average of 79.19 with the highest score of 94 and the lowest score of 70. The conclusion from this study is that learning by applying the guided discovery model can improve results, as well as the learning activities of class VII students .2 Public Middle School 4 Lahat. ABSTRAKPenerapan model penemuan terbimbing diharapkan dapat meningkatkan hasil belajar serta meningkatkan perhatian dan aktivitas siswa pada proses pembelajaran. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar belajar siswa setelah diterapkannya model penemuan terbimbing, serta meningkatkan proses pembelajaran yang dilakukan di kelas, dan meningkatkan kinerja guru,Penelitian ini menggunakan penelitian tindakan kelas (classroom action research) sebanyak tiga siklus. Setiap siklus terdiri dari empat tahap yaitu: rancangan, kegiatan dan pengamatan, refleksi, dan refisi. Sasaran penelitian ini adalah siswa kelas VII.2. Data yang diperoleh berupa hasil tes akhir, lembar observasi kegiatan belajar mengajar. Hasil penelitian menunjukan bahwa penerapan model penemuan terbimbing telah meningkatkan hasil belajar siswa. Peningkatan tersebut dapat dilihat dengan rincian 55,56% pada siklus I dengan rata-rata kelas 71,15, dengan nilai tertinggi 80 dan nilai terendah 50. Pada siklus II 74,07% dengan rata-rata kelas 74,67 dengan nilai tertinggi 85 dan nilai terendah 60 dan pada siklus III 92,59% dengan rata-rata kelas 79,19 dengan nilai tertinggi 94 dan nilai terendah 70. Kesimpulan dari penelitian ini adalah pembelajaran dengan diterapkan model penemuan terbimbing dapat meningkatkan hasil, serta aktivitas belajar siswa kelas VII.2 SMP Negeri 4 Lahat.